Baicalin ameliorates polycystic ovary syndrome through AMP-activated protein kinase - Wei Wang; Jiahua Zheng; Na Cui; Lei Jiang; Han Zhou; Dan Zhang; Guimin Hao (BMC, 2019)
Abstract Polycystic ovary syndrome (PCOS) is a complex endocrine disorder and regarded as the leading cause of anovulatory infertility. PCOS is characterized by reproductive dysfunction and metabolic disorders. Baicalin (BAL) is one of the most potent bioactive flavonoids isolated from the radix of Scutellaria baicalensis. In the present study, we investigated the potential effects of BAL on PCOS in dehydroepiandrosterone-treated rats. We found that BAL notably reduced the serum levels of free testosterone, total testosterone, follicle-stimulating hormone, luteinizing hormone, progesterone, and estradiol in PCOS rats. The increase of serum insulin level and HOMA-IR was markedly inhibited by BAL. Moreover, BAL decreased body weights, increased the number of rats with the regular estrous cycle, and ameliorated ovarian histological changes and follicular development in the DHEA-treated PCOS rats. The increase of pro-inflammatory cytokines (TNFα, IL-1β, and IL-18) and decrease of anti-inflammatory cytokine (IL-10) in PCOS rats were suppressed by BAL. BAL induced a significant decrease in the mRNA expression of steroidogenic enzymes, including 3β-HSD, CYP11A1, CYP19A1, StAR, in ovarian tissues in PCOS rats. Furthermore, BAL inhibited the decrease of AMPK protein level and phosphorylation, the decrease of Akt phosphorylation and the increase of 5α-reductase enzyme 1 expression in ovarian tissues in PCOS rats. The effects of BAL were inhibited by an inhibitor of AMPK, dorsomorphin. The upregulation of AMPK contributed to the beneficial effects of BAL. The results highlight the potential role of BAL for the intervention of PCOS.